Effect of 940nm Diode Laser Irradiation on Microtensile Bond Strength of an Etch and Rinse Adhesive (Single Bond 2) to Dentin - Shahin Kasraei; Ebrahim Yarmohamadi; Pegah Ranjbaran Jahromi; Mahdi Akbarzadeh (Journal of Dentistry, 2019)
Statement of the Problem: Laser can influence bonding mechanism by increasing the penetration depth of adhesive in smear layer. The effect of 940 nm diode laser on microtensile bond strength of adhesive to dentin has not been investigated in previous studies. Purpose: The aim of this study was to evaluate the effect of 940 nm diode laser irradiation on microtensile bond strength of Single Bond 2 to dentin. Materials and Method: Thirty sound premolars extracted for orthodontic reasons were randomly divided into five groups as follows: G1 or control: etching+ Single Bond2 (SB); G2: diode laser (940 nm wavelength, 1W power, continuous mode)+ etching+ SB; G3: etching+ laser irradiation+ SB; G4: etching+ SB+ laser irradiation+ adhesive curing; G5: etching+ laser irradiation+ SB +laser irradiation +adhesive curing. After the bonding procedure, Z250 composite resin was applied on the dentin surface in three layers of 2 mm thickness. After 24 hours of immersion in distilled water at 37°C and thermocycling for 1000 thermal cycles, the teeth were sectioned into 1mm2 sticks. The microtensile bond strength was measured using a universal testing machine. Bond strength (MPs) was analyzed by one-way ANOVA followed by HSD post hoc Tukey’s test (α=0.05). Results: G4 (38.35±8.99) showed the significant highest bond strength compared to other groups (p= 0.000). G5 (25.16±6.14) showed significantly higher bondstrength than the control group (18.85±4.79) (p= 0.032).Bond strength of G2 (23.39±6.07) and G3 (22.85±5.11) groups was the same and similar to that in the control group (p> 0.05). Conclusion: Based on the results of this study, it may be concluded that dentin surface irradiation with 940 nm diode laser after adhesive application and prior to curing can significantly increase the bond strength of composite to dentin.